2018
DOI: 10.1111/apa.14318
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia was common in acute gastroenteritis in a prospective hospital‐based study, but electrolyte imbalances were not

Abstract: Hypoglycaemia was common in acute gastroenteritis, but major electrolyte disturbances were infrequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
4
2
0
1
Order By: Relevance
“…The majority of children were more likely to present at the hospital early with a length of illness less than 2 days, which was also similar to ndings in previous studies [6, 7]. Consistent with previous pediatric studies [7,11,12], most patients (74.9%) in this study had mild-to-moderate dehydration at presentation. Viruses have been found to be the main cause of AGE in children [1,16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of children were more likely to present at the hospital early with a length of illness less than 2 days, which was also similar to ndings in previous studies [6, 7]. Consistent with previous pediatric studies [7,11,12], most patients (74.9%) in this study had mild-to-moderate dehydration at presentation. Viruses have been found to be the main cause of AGE in children [1,16].…”
Section: Discussionsupporting
confidence: 91%
“…This study demonstrated a predominance of males (59.4%), as in previous pediatric series [7,8,11,12]. The majority of children were more likely to present at the hospital early with a length of illness less than 2 days, which was also similar to ndings in previous studies [6, 7].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, children from our series had significant glucose, electrolyte and acid-base abnormalities, which is not that common according to other studies. 21,22 Qadori et al 26 found an association between the duration of vomiting and the risk of hypoglycemia, which could explain hypoglycemia episodes in our patients, too.…”
Section: Discussionsupporting
confidence: 54%
“…BUN, creatinine, and blood gases (pH, serum bicarbonate) were discovered to be useful clinical markers to determine dehydration and severity in children with acute gastroenteritis (17)(18)(19). Higher levels of creatinine, BUN, potassium, and lower glucose, pH, bicarbonate, albumin levels in severe group were related to the serious dehydration and acidosis.…”
Section: Discussionmentioning
confidence: 99%